Analisis Peningkatan Kontrol Inventaris Kantor PT. Berkah Multi Cargo Melalui Strategi Business Process Mapping - Oktafiyan Dwi Saputra; Abdurrahman Faris Indriya Himawan (CERED Indonesia Institute, 2022)
Inventory data processing at the operational office of PT. BMC Logistics is still experiencing many problems because the process is still done manually, so it is not efficient and inventory control is difficult to do. This study aims to analyze how the Business Process Mapping contained in the company. The method used is using Business Process Mapping Notation and involves a qualitative method with a descriptive approach and data collection is done by direct observation and interviews. Informants were determined by purposive sampling. The results of the research will be the main design for office inventory management information system implementation that will soon be applied.